Changes in cardiovascular risk factors and health behaviours from 1992 to 1997 in the Republic of Karelia, Russia - Laatikainen, Tiina; Delong, Laura; Pokusajeva, Svetlana; Uhanov, Mihail; Vartiainen, Erkki; Puska, Pekka (The European Journal of Public Health, 2002)
Background: In Russia rapid changes have taken place both in total and chronic disease mortality during recent years. Little reliable information is available on the trends in conventional risk factors in Russia. Methods: Chronic disease risk factors and health behaviours were studied in the Republic of Karelia, Russia in 1992 and 1997, in population surveys connected with the National FINRISK Study in Finland. Independent random population samples (n=1000) of people aged between 25 and 64 years were drawn in both survey years. Surveys included a self‐administered questionnaire, physical measurements and laboratory analyses. Results: The levels of systolic blood pressure, total serum cholesterol, and high‐density lipoprotein cholesterol decreased among both genders from 1992 to 1997, but the difference between the survey years was statistically significant only among women. Both self‐reported alcohol consumption and serum gamma‐glutamyl transferase levels increased significantly in both men and women. There was a significant shift in the type of fat used on bread and in cooking, from butter use to use of margarine and vegetable oil, among both genders. Conclusions: As a whole the risk factor levels in the Republic of Karelia are high. However, some slight improvement in risk profile was seen. Positive changes in dietary habits, such as change in the quality of fat and associated reduction in serum cholesterol levels may have contributed to the decline in cardiovascular disease mortality seen in Russia since 1995. However, since smoking and elevated blood pressure levels as well as alcohol consumption are still highly prevalent, there is a great need for effective interventions.